Use of abdominal negative pressure wound therapy in different indications: a case series - EROL, BÜLENT; SAÇAK, BÜLENT; DURMUŞ KOCAASLAN, FATMA NİHAL; ÇELEBİLER, ÖZHAN BEKİR; AKDENİZ DOĞAN, ZEYNEP DENİZ (MA HEALTHCARE LTD, 2019)
Negative pressure wound therapy (NPWT) is a widely used wound management system. Several articles have been published on the advantages and complications of this system. Abdominal dressing negative pressure system (abdominal NPWT) is a newer technology, developed and used in open abdomen cases. The adherence of the sponge to the intra-abdominal organs is prevented by a polyurethane foam. This study presents a number of case series where an abdominal NPWT (ABThera, KCl, US) has been used to treat other vital organs, helping to prevent complications such as organ rupture and fatal bleeding.
Keywords: abdominal negative pressure wound therapy; ABThera; vacuum assisted closure therapy; VACUUM-ASSISTED CLOSURE; VAC(R) THERAPY; POSTPNEUMONECTOMY; MANAGEMENT; DEVICE; RISK